Mechanical behavior of in vitro blood clots and the implications for acute ischemic stroke treatment. (28th November 2019) - Johnson, Sarah; Chueh, Juyu; Gounis, Matthew J; McCarthy, Ray; McGarry, J Patrick; McHugh, Peter E; Gilvarry, Michael
Abstract : Background: Clot mechanical properties are influenced by composition and the arrangement of components within the clot. This work investigates the effects of platelet-driven contraction on blood clot microstructure and mechanical behavior, and provides insight into some implications for mechanical thrombectomy. Methods: Platelet-contracted clot analogues (PCCs) and non-contracted clot analogues (NCCs) were prepared from blood mixtures of various hematocrits (%H), that is, the volume percentage of red blood cells (RBCs) in the mixture. Mechanical testing was performed to compare the behavior of the analogues with previously tested human thromboemboli. Scanning electron microscopy and histology investigated the clot microstructure and composition. The association between clot properties and their behavior during mechanical behavior was also investigated. Results: Overall, PCCs were found to be stiffer than NCCs, across all hematocrits. PCCs with a low %H resisted complete ingestion via contact aspiration alone or complete retrieval with stent-retrievers. PCCs with a higher %H and all NCCs were fully retrievable, although the likelihood of fragmentation was increased in clots with a greater %H. Histologically, there was little difference in the RBC and fibrin content between PCCs and NCCs with the same %H. However, the microstructure of the two groups differed significantly. Conclusion: A selection of repeatable clot analogues with a range of mechanical properties have been developed for in vitro modeling of acute ischemic stroke. Platelet contraction significantly affects clot volume and microstructure, and in turn clot stiffness. The significant difference in mechanical properties and microstructure, but without an appreciable difference in histology, implies that histological studies of explanted human clots alone may not prove to be predictive of the mechanical behavior of the clots in thrombectomy.